(untitled) (Journal of Medical & Health Sciences Review, 2025)
The study rigorously investigates the clinical utility and efficacy of nursing interventions based on Traditional Chinese Medicine (TCM) in treating patients suffering from gynecological irregular menstruation. The primary objective is to assess not only the impact on menstrual regularity but also the overall psychological well-being and quality of life of the affected individuals. Conducted at the Pingxiang Maternal and Child Health Hospital in Jiangxi, China, the research employs a multifaceted, comprehensive approach. It combines traditional TCM therapies—herbal remedies, acupuncture—with modern medical assessments to offer a holistic treatment plan. Participants, after a thorough diagnostic evaluation, received individually tailored care plans that included dietary guidance and lifestyle recommendations. The study yielded encouraging results, with significant improvements in menstrual regularity and a reduction in associated symptoms among the participants. Moreover, the study found that the holistic care model of TCM contributed to enhanced psychological well-being and overall quality of life for the patients. Furthermore, the TCM-based nursing interventions resulted in higher patient compliance, greater satisfaction, and fewer instances of recurring illness. The compelling findings support the integration of TCM-based nursing interventions into contemporary healthcare practices, especially for gynecological issues. The study not only suggests the potential for improved patient outcomes but also emphasizes the need for future research to further validate these promising results. The study thus lays the groundwork for further research and potential healthcare policy changes.